Cases of acute gastroenteritis due to calicivirus in outbreaks: clinical differences by age and aetiological agent. (21st January 2014) - Sala, M. R.; Broner, S.; Moreno, A.; Arias, C.; Godoy, P.; Minguell, S.; Martínez, A.; Torner, N.; Bartolomé, R.; de Simón, M.; Guix, S.; Domínguez, A.; et al.
Abstract The Caliciviridae family includes norovirus and sapovirus, which both cause acute gastroenteritis (AGE). Currently, norovirus is the most common cause of AGE in all age groups in many countries. We analysed clinical differences in reported cases of acute gastroenteritis caused by caliciviruses (AGC) by age group and agent involved. We conducted a descriptive study of AGE outbreaks reported to the Public Health Agency of Catalonia (Spain) in 2010 and 2011. The odds ratios (ORs) and corresponding 95% confidence intervals (CIs) were calculated to estimate the association between clinical symptoms and age. Clinical differences between the <15 years and ≥15 years age groups were statistically significant: children more frequently presented with vomiting (OR, 3.25; 95% CI, 2.56–4.13), abdominal pain (OR, 3.27; 95% CI, 2.60–4.12), fever (OR, 1.51; 95% CI, 1.17–1.96) and nausea (OR, 1.49; 95% CI, 1.19–1.85). Comparing clinical manifestations of sapovirus and norovirus infection in children aged <15 years, cases caused by norovirus more frequently presented with vomiting and fever (p <0.001), and cases caused by sapovirus more frequently presented with diarrhoea (p 0.013). Determination of the clinical differences associated with cases in outbreaks according to the age of the majority of cases and the symptoms most frequently detected may aid decision making and guide aetiological investigations and the adoption of prevention and control measures.